Biological Indicators Reveal Small-Scale Sea-Level Variability During MIS 5e (Sur, Sultanate of Oman). (13th January 2020) - Falkenroth, M.; Adolphs, S.; Cahnbley, M.; Bagci, H.; Kázmér, M.; Mechernich, S.; Hoffmann, G.
In this study we aim to document various coastal notches in Sur Lagoon (Oman) and interpret them regarding their use as sea-level indicator. We also unravel any short-term sea-level fluctuations, which are potentially preserved within the trace fossil assemblages of some of the notches. The oldest paleo notches stem from the last interglacial sea-level highstand of MIS 5e. This is concluded from cosmogenic nuclide dating of the fanglomerate bedrock in Sur Lagoon as presented in this study. All outcrops of paleo notches around Sur Lagoon were investigated in regards to the faunal distribution and notch shape. Furthermore, the absolute elevation of the notches and biological markers relative to msl were measured with a differential GPS. The bioerosional notch occurs at the same height around Sur Lagoon indicating that the area remained tectonically stable over the last 125 kyr. According to the elevation of the notch-apex, msl was 3.93 ± 0.12 m higher than today during the last interglacial. The distribution of boring and bioconstructing organisms relative to the notch shape displays at least one phase of short-term sea-level rise subsequent to the notch formation. The beachrocks that are associated with the bioerosion notches in Sur Lagoon show a larger grainsize than any sediment that is deposited in the lagoon nowadays. This, in combination with the occurrence of exceptionally high and deep abrasion notches, indicates that the coastline was more openly exposed and thus experienced a higher wave energy during the notch formation.